Review of plagiarism detection and control & copyri ghts in India - Prof. S.S.Karadage; Prof. Mahesh S. Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
Plagiarism software’s has been in use for almost a decade to get the sense of “theft of intellectual property". However, in today’s digital world the easy access to the web, lar ge databases, and telecommunication in general, has turned plagiarism into a serious problem for publishers, researc hers and educational institutions. The first part of this paper discusses the different plagiarism detection techni ques such as text based, citation based and shape based and compared with respect of their features and performance and an overview of different plagiarism detection methods used for text documents have taken. The second half of the paper is fully dedicated to copyrights in India